VFSMOD-based Simulation and Analysis of Sediment Retention Effect of Vegetative Filter Strip - ZHANG Yuyang; SUN Zheng; CAI Guoqiang; NIE Shihao; ZHANG Liang; ZONG Quanli (Renmin Zhujiang)
Taking four typical vegetative filter strips in the Beichahe Village section,Renzhao Town sluice section,Chengjiaxiaoli Village section,and Houlujia Village section in the Dagu River Basin of Shandong Province as examples,this paper simulates the sediment retention effect with the vegetative filter strip model (VFSMOD).VFSMOD is applied to examine the sensitivity of the width,length,slope,vegetation spacing,and vegetation roughness of the vegetative filter strips to the sediment retention effect and compare the sensitivity of sediment retention rate to the five parameters in four typical locations. The results show that sediment retention rate is positively correlated with the width of the filter strip,and the influence is obvious before the width reaches 5 m.Sediment retention rate is also positively correlated with the length of the filter strip.When the length of the filter strips in Beichahe Village,Renzhao Town,and Chengjiaxiaoli Village reaches 20 m,the impact of strip length on sediment retention rate decreases.In contrast,the impact of the length of the filter strip in Houlujia Village on the sediment retention rate is relatively stable.Sediment retention rate is negatively correlated with vegetation spacing,and the influence is obvious before vegetation spacing reaches 10 cm.The correlation between sediment retention rate and the slope is also negative,and after the slope reaches 0.05,the retention rate is basically no longer affected by it. Sediment retention rate is negatively correlated with vegetation roughness as well,although this impact is small.This study not only provides methods and theoretical data for investigating the soil loss in the Dagu River but also serves as a reference for analyzing similar rivers in China.